Clinical Features and Dynamics of T Cells-Related Markers in Immunocompetent Patients with Cytomegalovirus Hepatitis. (30th August 2020) - Komura, Takuya; Kagaya, Takashi; Takayama, Hideo; Yanagi, Masahiro; Yoshio, Takatoshi; Sugimoto, Saiho; Nishino, Michiko; Orita, Noriaki; Asahina, Yoshiro; Nishikawa, Masashi; Kaneko, Shuichi; Unoura, Masashi
Abstract : Aim . Cytomegalovirus (CMV) can cause hepatitis, encephalomyelitis, and pneumonitis in immunocompromised patients. In contrast, CMV infection of immunocompetent patients can lead to the development of infectious mononucleosis and is typically self-limiting; severe complications are rare. We evaluated the pathophysiology and immunological aspects of CMV hepatitis in recently immunocompetent adult patients. Methods . We examined the clinical features and outcomes of 47 adult immunocompetent patients with CMV hepatitis (29 men, 18 women; mean age, 34 ± 11 years) from January 2005 to August 2019 treated in our hospital. We also assayed T-cell activation to evaluate the immune responses in these patients. Results . Fever (74.5%), hepatosplenomegaly (74.5%), sore throat (36.2%), headache (31.9%), abdominal pain (27.7%), lymphadenopathy (23.4%), and skin rash (6.4%) were present at admission. Complications included gastrointestinal injury (25.5%), neuropathy (4.3%), thrombocytopenia (2.1%), and splenic infarction (2.1%). All patients had a good clinical course without liver failure or transition to chronic liver injury. The time to recover from liver injury ranged from 12 to 142 days (mean, 43.4 ± 28.7 days). The serum sIL-2R level, which reflects T-cell activation, was transiently elevated and correlated with the extent of hepatic inflammation. Conclusions . CMV hepatitis in immunocompetent individuals has a satisfactory outcome, but occasionally results in complications in other organs. The sIL-2R level has potential as a surrogate marker of hepatic inflammation in immunocompetent patients with CMV hepatitis.